2010
DOI: 10.1002/uog.7584
|View full text |Cite
|
Sign up to set email alerts
|

Tei index to assess fetal cardiac performance in fetuses at risk for fetal inflammatory response syndrome

Abstract: Objectives To examine, in patients with premature rupture of the amniotic membranes (PROM) at < 34 weeks of gestation, the relationship between fetal myocardial performance measured by the Tei index and fetal inflammatory response syndrome (FIRS). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 72 publications
1
30
1
2
Order By: Relevance
“…The effect of several other fetal pathologies on MPI have also been evaluated [35,36,37,38,104,105,106,107,108,109,110,111,112,113]. Romero et al [113] demonstrated abnormal cardiac function in fetuses with pre-term rupture of membranes and positive microbial cultures in the amniotic fluid.…”
Section: Clinical Application Of Mpimentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of several other fetal pathologies on MPI have also been evaluated [35,36,37,38,104,105,106,107,108,109,110,111,112,113]. Romero et al [113] demonstrated abnormal cardiac function in fetuses with pre-term rupture of membranes and positive microbial cultures in the amniotic fluid.…”
Section: Clinical Application Of Mpimentioning
confidence: 99%
“…Romero et al [113] demonstrated abnormal cardiac function in fetuses with pre-term rupture of membranes and positive microbial cultures in the amniotic fluid. Additionally, increased MPI values have been shown in fetuses with signs of fetal inflammatory response syndrome [36]. …”
Section: Clinical Application Of Mpimentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm rupture of membranes, particularly in cases with intra-amniotic infection, is associated with changes in fetal cardiac function consistent with increased left ventricular compliance and systolic dysfunction measured as an increased E/A ratio [131,132], shorter ejection time [133], and ventricular strain [132]. …”
Section: Research and Clinical Applications Of Fetal Cardiac Functionmentioning
confidence: 99%
“…Friedman et al [4] first used the same cardiac cycle by defining a different position of the Doppler sample volume, and then Hernandez-Andrade et al [5] in 2005 proposed a modified MPI (Mod-MPI) based on the use of mitral (MV) and aortic valve (AoV) clicks as landmarks for the measurement of time intervals. There has been subsequent growth in research into fetal MPI for application in normal and complicated pregnancies [6,7,8,9,10,11]. Although individual units have demonstrated reproducibility in fetuses [5,12], published normal ranges have been widely variable, causing concern as to the validity of this new technique.…”
Section: Introductionmentioning
confidence: 99%